Optical and Structural Properties of Insoluble and Flexible Biodegradable Regenerated Silk Films for Optically Transparent Hydrophilic Coating of Medical Devices - Supranee Kaewpirom; Siridech Boonsang (Advanced Materials Interfaces, 2022)
Abstract Many medical equipment, such as tubes, lenses, and disposable plastic slides, require improved wettability to perform properly with physiological fluids and tissues. The authors proposes the regeneration of silk cocoons into insoluble and flexible regenerated silk fibroin (SF) films allowed for the development of novel materials with distinct and convincing characteristics. The SF films with glycerol modifications are created using a casting/solvent evaporation technique to provide a flexible and optically transparent hydrophilic coating. Fourier‐transformed infrared spectroscopy and wide‐angle X‐ray diffraction reveal a structural shift in glycerol‐induced SF films, where the random coil and helical structure content reduce while the β‐sheet structure increases significantly. All of the proposed SF films have an outstanding transmission of approximately 90% in the visible range and a UV‐shield characteristic. Tensile tests reveal that glycerol‐plasticized SF films are soft and extremely flexible, with a high Young's modulus and moderate tensile strength. The adhesion strength of the SF films is assessed as 5B at 10–20% wt of glycerol, suggesting outstanding adhesion strength on the silanized glass surface. At 30% w/w glycerol, the SF film has the greatest swelling ratio of 95.3 ± 0.5% and the lowest water contact angle of 23.2°.
Keywords: Silk-based biomaterials and applications; Electrospun Nanofibers in Biomedical Applications; Polymer Surface Interaction Studies